2015
DOI: 10.1080/09500693.2015.1054000
|View full text |Cite
|
Sign up to set email alerts
|

Student Decision-Making about a Globally Familiar Socioscientific Issue: The value of sharing and comparing views with international counterparts

Abstract: This paper focuses on the views of 16-17-year-old science students from England, Germany, Hong Kong and Sweden on whale hunting, and their perceptions of the views of their international counterparts. The students were all provided with the same decision making task, discussed the issue in small groups and then presented their views on video, which were shared with their counterparts. The findings show that the decision making task served to deepen and modify students' views across all nationalities, and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
6
1
4
Order By: Relevance
“…With regard to the literature on SSIs, studies mostly examined producing arguments in SSIs (Cetin, Dogan & Kutluca, 2014;Molinatti, Girault & Hammond, 2010), developing argumentation skills related to SSIs (Dawson & Venville, 2013;Grooms et al, 2014;Kortland, 1996;Zohar & Nemet, 2002), decision-making processes for SSIs (Evagorou et al, 2012;Grace, Lee, Asshoff & Wallin, 2015;Sakschewski et al, 2014), and informal reasoning and the factors affecting it (Sadler, 2003;Sadler & Zeidler, 2005a, b;Topcu et al, 2011). The data in related studies were gathered from middle school (Emery, Harlow, Whitmer & Gaines, 2017;Khishfe, 2014;Patronis et al, 1999), high school (Dawson & Carson, 2017;Kolarova, Hadjiali & Denev, 2013), preservice (Grooms et al, 2014;Topcu et al, 2011;Ozturk & Yilmaz-Tuzun, 2017), and inservice teachers (Day & Bryce, 2011;Liu & Roehrig, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the literature on SSIs, studies mostly examined producing arguments in SSIs (Cetin, Dogan & Kutluca, 2014;Molinatti, Girault & Hammond, 2010), developing argumentation skills related to SSIs (Dawson & Venville, 2013;Grooms et al, 2014;Kortland, 1996;Zohar & Nemet, 2002), decision-making processes for SSIs (Evagorou et al, 2012;Grace, Lee, Asshoff & Wallin, 2015;Sakschewski et al, 2014), and informal reasoning and the factors affecting it (Sadler, 2003;Sadler & Zeidler, 2005a, b;Topcu et al, 2011). The data in related studies were gathered from middle school (Emery, Harlow, Whitmer & Gaines, 2017;Khishfe, 2014;Patronis et al, 1999), high school (Dawson & Carson, 2017;Kolarova, Hadjiali & Denev, 2013), preservice (Grooms et al, 2014;Topcu et al, 2011;Ozturk & Yilmaz-Tuzun, 2017), and inservice teachers (Day & Bryce, 2011;Liu & Roehrig, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This implied that they supported their decisions with scientific evidence and content knowledge from genetics. However, previous studies have shown that school students used relatively limited knowledge or scientific evidence to support their decisions (Bell & Lederman, 2003;Christenson et al, 2012Christenson et al, , 2014Grace et al, 2015). Several factors may explain the difference in scientific knowledge use between two groups (students and PTs): PTs are older than school students, have learned more science content, and they most likely know that they need to be using this in their future science teaching.…”
Section: Pre-service Teachers' Use Of Multiple Subject Areas In Decision-makingmentioning
confidence: 99%
“…Como señalan Osborne, Erduran, Simon y Monk (2001), que un estudiante cambie su forma de pensar sobre una cuestión es un indicador de calidad, pero solo es posible si se proporcionan oportunidades para el intercambio de opiniones a través de la discusión (Grace et al, 2015). En este estudio utilizamos como estrategia de intercambio de opiniones el juego de rol.…”
Section: Marco Teóricounclassified